Hubungan Kadar Matrix Metalloproteinase-8 (MMP-8) pada Pasien Gingivitis Setelah Tindakan Scaling dan Root Planing Berdasarkan Gingival Index (GI) - Thifla Rafifa Wirza; Nita Afriani; Nila Kasuma (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
This study aims to analyze the relationship between the Gingival Index (GI) and the levels of Matrix Metalloproteinase-8 (MMP-8) in the saliva of gingivitis patients after Scaling and Root Planing (SRP). A total of 36 gingivitis patients aged 15-24 years who underwent SRP in Padang City were included in the study. GI was assessed using the WHO probe, and saliva samples were collected on day 7 after SRP using the unstimulated saliva method. MMP-8 levels in the saliva were analyzed using an ELISA kit. The results showed higher average MMP-8 levels in the moderate and severe gingivitis groups compared to the mild group, but with considerable individual variation. The Kruskal-Wallis test revealed that the difference in MMP-8 levels among GI categories was not statistically significant (p = 0.584). Although there was a trend of increasing levels, these results suggest that MMP-8 cannot be used as a sole determinant of gingivitis severity and is better utilized as a supportive biomarker when combined with other clinical parameters.